1983
DOI: 10.1002/bem.2250040308
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of T‐lymphocyte cytotoxicity following exposure to sinusoidally amplitude‐modulated fields

Abstract: Significant inhibition of allogeneic cytotoxicity of the target cell MPC-11 by the murine cytotoxic T-lymphocyte line CTLL-1 was observed when the 4-h cytotoxicity assay was conducted in the presence of a 450-MHz field sinusoidally amplitude-modulated at 60 Hz. Exposure of the effector cells to the field prior to adding them to the target cells in the cytolytic assay resulted in a similar inhibition, suggesting a direct interaction of the field with the cytolytic T lymphocyte. The inhibition was preferentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…The (14) and in its synaptosomal fractions (15) and are similarly ineffective in modulating cell-mediated cytotoxicity of T lymphocytes (16), phenomena that are -strongly responsive to radio and microwave fields amplitude modulated at frequencies <100 Hz. We have confirmed that these fields produced an electrical gradient of ==I.O mV/cm around a 1-cm ioop in the spatially homogeneous portion ofthe field between the coils and that the expected peak extracellular current density in homogeneous conducting electrolytes would be =zzl.0 pA/cm2 ('13 (6).…”
Section: Methodsmentioning
confidence: 99%
“…The (14) and in its synaptosomal fractions (15) and are similarly ineffective in modulating cell-mediated cytotoxicity of T lymphocytes (16), phenomena that are -strongly responsive to radio and microwave fields amplitude modulated at frequencies <100 Hz. We have confirmed that these fields produced an electrical gradient of ==I.O mV/cm around a 1-cm ioop in the spatially homogeneous portion ofthe field between the coils and that the expected peak extracellular current density in homogeneous conducting electrolytes would be =zzl.0 pA/cm2 ('13 (6).…”
Section: Methodsmentioning
confidence: 99%
“…Hamrick and Fox [1977] exposed cultures of rat lymphocytes, and found the differences between the RFEMF and control cultures nonsignificant. Lyle et al [1983] sought effects for 60 Hz amplitude modulated 450 MHz RFEMF at 1.5 mW/cm 2 (SAR not stated) on the toxicity of certain rodent T-lymphocytes (effector cells) against lymphoma cells (target cells) of a specific type. The authors surmised that cytotoxicity was due to the action of the RFEMF on the effector cells.…”
Section: Leukocytes (White Blood Cells)mentioning
confidence: 99%
“…At low levels, experimental demonstrations include behavioural changes in continuous-wave or modulated fields (Shandala, 1977), altered efflux of calcium from brain tissue exposed to extremely low frequency modulated waves (Blackman, et al, 1979;Blackman, 1980), changes in EEG waves (Takashima, 1979), impaired killing ability of lymphocytes (Lyle, 1983), chromosomal changes in developing mouse sperm cells, changes in intracellular enzyme activity, altered firing rate of molluscan pacemaker neurons (Seaman and Wachtel, 1978), and changes in growth rate of yeast cells. Furthermore, athermal mechanisms are proposed for rectification by cell membranes (Pickard and Rosenbaum, 1978), which has been observed in plant cells at frequencies below 10 MHz; vibrational resonance in DNA molecules (Edwards, 1984); and structural transformations from random to coiled configurations in polymeric proteins.…”
Section: Introductionmentioning
confidence: 99%